IDDF2020-ABS-0110 lncRNA MNX1-AS1 promotes the progression of colorectal cancer through stabilizing YB1. (18th November 2020) - Wu, Qinian; Luo, Xiaojing; Liu, Jia; Zhao, Qi; Lu, Yunxin; Wang, Yun; Ju, Huaiqiang; Xu, Ruihua
Abstract : Background: Improving the prognosis of Colorectal Cancer (CRC) depends on the identification of the mechanisms of recurrence and metastasis, and developing new therapeutic targets. lncRNA has become an attractive potential therapeutic target because it is more precise and less toxic when compared with traditional protein targeted drugs. We aimed to identify novel lincRNAs that significantly affects the development of CRC, and investigate the potential associated therapeutic targets. Methods: Based on RNA-seq analysis, we screened out ten candidates and identified highly expressed lncRNAs in the 21 CRC tissue samples. An siRNA library was established to identify lncRNAs that significantly affected CRC cell proliferation and metastasis. RT-PCR and RNAi assays were performed to investigate the functional role of lncRNA MNX1-AS1 and clinical relevance. In vivo, cell-based and patient-derived xenograft (PDX) models were used to further explore roles of MNX1-AS1 in CRC tumorigenesis, metastasis and potential therapeutic target. RNA pull-down, mass spectrometry analyses, western blot and RNA-binding protein immunoprecipitation (RIP), DNA-binding protein immunoprecipitation (Chip), and Double Luciferase Report experiment were performed to identify interaction proteins and related mechanisms. Results: MNX1-AS1 was upregulated in CRC tissues from patients with poor overall survival (OS), and MNX1-AS1 inhibition led to the impaired CRC cell line growth. Moreover, knockdown of MNX1-AS1 resulted in a decreased level of Y-box binding protein 1 (YB1), a multifunctional RNA/DNA binding protein. MNX1-AS1 blocked ubiquitination of YB1 and maintained its stability. This process prevented the degradation of YB1 through the MYC pathway. Therefore, knockdown of MNX1-AS1 attenuated the downstream effects of YB1. In addition, the transcription of MNX1-AS1 could be inhibited by MYC in CRC cells. In vivo experiments showed that the inhibition of MNX1-AS1 suppressed the proliferation of tumors in orthotopic models and patient-derived xenograft (PDX) models. Conclusions: The newly identified MNX1-AS1, which is regulated by MYC, plays a pivotal role in CRC proliferation by enhancing YB1 stability, thus facilitating the development of CRC. Collectively, our study suggests that MYC- MNX1-AS1-YB1 axis might serve as potential biomarkers and therapeutic targets in CRC treatment.